Tênis em cadeira de rodas: sistematização, aplicação e avaliação de um programa de ensino - Quidim, Fernanda Gabriela (2013)
Pedagogical aspects related to systematization and evaluation within the process of teaching and learning in the Wheelchair Tennis (WCT) has been demonstrated in some scientific studies. This fact is justified by this modality being considered a recent practice, verified by shortages of professionals and little supply of WCT programs, beyond the vision that it is an elitist sport. Based on these factors and knowing the importance of a structured, systematic and assessment in sport teaching, this study aims at evaluating the influence of a program in Wheelchair Tennis on the specific skills of the sport in people with physical disabilities. Study participants are 4 males, with ages ranging from 19 to 53 years old, whose main common characteristic is physical disability (spinal cord injury, sequelae of poliomyelitis or amputation) and no previous experience with tennis. This study is characterized as a field survey of the exploratory type with experimental manipulation. The intervention was implemented in a 12-week period involving training of 1 hour duration. For data collection was used in Performance Assessment in Wheelchair Tennis (PAWCT) (developed by the researcher) to evaluate the effectiveness of the fundamentals of the WCT programs. It was also used a diary to record the evolution of individual participants and the aspects of the CCT program. The analysis was based on descriptive and statistical analyzes. The program influenced in approximately 93% of the skills studied and there was an improvement of them. The smash, volley, serve and backhand were the fundamentals that presented the highest statistically significant increases. Individual analysis allows us to trace personal evolution for each fundamental demonstrating not only the answers to the program, but the relationship between each etiology and characteristics of learning.